CRESCIMENTO INICIAL DO MAMOEIRO EM DIFERENTES NÍVEIS DE SOMBREAMENTO E SUBSTRATOS - SALLES, Josiane Souza; COSTA, Edilson; LIMA, Alexandre Henrique Freitas; SILVA, Bruna Luzia Barbosa; FERREIRA, Thales Silva; PAULA, Fernando Oliveira (ANAIS DO ENIC, 2017)
-